Optimization of metal polymer friction pair composition for hydrogen wear reduction through thermal stabilization analysis - Dmytro Volchenko; Ivan Kernytskyy; Yuriy Royko; Mykola Ostashuk; Nataliia Fidrovska; Vasyl Skrypnyk; Dmytro Zhuravlev; Nataliia Klochko; Vasyl Rys; Oksana Berezovetska; Saurav Dixit; Anna Stefańska; et al. (Scientific Reports)
Abstract The composition of the metal-polymer friction pair is carefully considered for interacting with water and hydrogen, ensuring the metals electrode process potential remains below waters in a neutral medium. Simultaneously, adherence to defined chemical composition ratios for the metal-polymer materials is crucial. This analysis is conducted under conditions of thermal stabilization, characterized by a minimal temperature gradient across the rim thickness within an equivalent thermal field. Using the quasi-chemical approximation, the paper derives a concentration-dependent diffusion coefficient of hydrogen (H) in iron (Fe) across a broad spectrum. This derivation includes electronic and vibrational contributions to the chemical potential. The research establishes a correlation between the equivalent diffusion coefficient and the concentration of diffusing hydrogen atoms from the metal, such as the pulley or drum rim. These findings offer novel insights into optimizing hydrogen wear behaviour in brake friction couples, contributing to advancements in materials and design considerations in the automotive field.